Correlation of Viral Load, Disease Severity and High Risk-Human PapillomaVirus (HR-HPV) in Abnormalities of Cervical Samples (Journal of the College of Basic Education, 2022)
Clinical and epidemiological studies have confirmed that high-risk human papillomavirus (HR-HPV) infection (genotypes 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58 59, and 68) is the direct cause of cervical intraepithelial neoplasia (CIN) and cancers. This study was designed to determine whether viral loads in relation with progression of HPV infections using real-time PCR. According to cytological test, 110 and 12 of suspected women with abnormal and normal cytologic changes were selected. Results showed that 35/110 and 2/12 women were positive for HR-HPV DNA. Results showed the median of viral load increasing in high-grade cervical intraepithelial neoplasia (CIN II, III and cancer) and associated with the severity of lesion (786 copies/ml equivalent for CIN II, 2,037,000 copies/ml equivalent for CIN III, and 956,840 copies/ml equivalent for invasive cancer). Meanwhile, the median of viral load in CIN I showed more 250-fold higher than that of HPV infected women with normal cytology (183,700 copies/ml equivalent for CIN I and 683 copies/ml equivalent for normal cytology). Although the viral load was increased with primary infection and specific genotypes, high viral load was accompanied with severity of disease.